Research on State Monitoring System of Intelligent Disconnecting Switch Based on Sensing Technology - Jinhong Chen; Guibin Wu; Xingzhan Jian; Liujun Cai; Shaoyong Chen; Rixin Chen (Frontiers in Energy Research, 2022)
The intelligentization, informationization, and internalization of power system infrastructure equipment are the key technologies to achieve the low-carbon transformation of the power system. To tackle the low degree of intelligence and the internet in the monitoring and early warning of mechanical faults of the disconnecting switch, this paper designs an intelligent monitoring system for the disconnecting switch operation status based on sensing technology. Torque sensors, angle encoders, micro-switches, attitude sensors, and temperature and humidity sensor technology are used to monitor the operation status of the disconnecting switch, and an advanced RISC machine (ARM) embedded terminal system is used as the disconnecting switch status monitoring center. The intelligent monitoring system aims to accurately monitor the temperature and humidity environment in the disconnector operating mechanism box, the opening and closing position state of the disconnector, and the torque angle variation characteristics of the disconnector according to the operating parameters collected by the sensor, while achieving remote real-time state monitoring of the disconnecting switch. The function tests and field tests show that the system performance is stable, and the state information collection, intelligent analysis, and remote monitoring meet the actual needs, which can improve the efficiency of disconnecting switch operation, maintenance, and overhaul, thereby reducing the risk of power grid outages.